Paget-Schroetter Syndrome - Sułkowski, L.; Pasternak, A.; Szura, M.; Matyja, A. (Phlebologie, 2015)
Paget-Schroetter Syndrome is a primary, effort vein thrombosis of the axillo-subclavian level. It occurs predominantly after repetitive sport movements in the dominant limb in young healthy male individuals. Patients refer with pain, swelling and blue discolouration in the affected upper extremity.We present a 33-years-old woman with primary thrombosis of left subclavian vein, with no history of repetitive sport exercises or trauma. The patient’s profession requiring leaning against the desk for hours daily could be a trigger factor for vein thrombosis in presented case. Doppler ultrasonography and venography showed complete occlusion of left subclavian vein. Computed tomography showed no evidence for compression at thoracic outlet level. Patient was successfully treated with anticoagulants and followed for 21 months with repeated duplex ultrasound examinations. The symptoms had resolved. Long time left subclavian vein patency and good quality of life have been achieved.
Keywords: Paget-Schroetter Syndrome; primary thrombosis; effort thrombosis; axillary vein; subclavian vein